Isolation and Selection of Extracellular Enzymes in Sponge Symbiont Bacteria (Porifera: Demospongiae) from Tablolong Beach - Dima, Lintang A. M.; Rafael, Andriani; Nge, Sonya T.M; Radjasa, Ocky K.; Manalu, Tiodor S. J.; Ngginak, James (Universitas Labuhanbatu, 2023)
Marine biota has many benefits for human life. Sponges are a species of marine biota that can be used as a producer of antimicrobial compounds. The bacteria found in sponges have an important role in the continuity of life in the sea. The symbiotic lifestyle that occurs in bacteria and sponges has the opportunity to form substitutions for the content of secondary metabolites and enzymes, especially extracellular enzymes (amylase, protease, cellulose and lipase). This study aims to determine how to isolate sponge symbiotic bacteria and identify spongy symbiotic bacteria. The method used is purposive to take sponges. Characterization of bacteria was carried out based on morphology and gram staining. Enzymatic bacterial selection was carried out by testing the activity of the amylase enzyme (soluble starch), lipase enzyme (Teen 80), protease enzyme (skim milk) and cellulose enzyme (carboxyl methyl cellulose). Data analysis was performed in a qualitative descriptive manner by measuring the clear zone in the extracellular enzyme test results. Meanwhile, other research parameters measured in this study were temperature, salinity and pH. The results showed that out of 47 isolated bacteria and 33 of them had extracellular enzymes with 10 bacteria had amylase enzymes, 27 bacteria had lipase enzymes, 2 bacteria had protease enzymes and 1 isolate had cellulose enzymes.